1959
DOI: 10.1017/s0022029900009912
|View full text |Cite
|
Sign up to set email alerts
|

The effect of heat on the vitamin B6 of milk: II. A comparison of biological and microbiological tests of evaporated milk

Abstract: Unsweetened evaporated milk is widely used in infant feeding. This product is subjected to drastic heat treatment during sterilization in the can. Lately there have been several reports (l, 2, 3, 4, 5, 6) that in the process of manufacture evaporated milk loses a large part of its original vitamin B 6 activity. According to Tomarelli, Spence & Bernhart(5) the loss of vitamin B 6 , as judged microbiologically, is much less than that determined with rats. We present here the results of a reinvestigation of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1959
1959
1995
1995

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…When the level of protein in the diets was increased to either 20% or as high as 50% of the total diet, growth-related parameters indicated higher responses to PN in the diet relative to PL and PM (Table V). It has been suggested in earlier work that intestinal microorganisms may preferentially utilize PL and PM in the diet, leading to decreased availability of and therefore decreased rat responses to dietary PL and PM (Waibel et al, 1952;Davies et al, 1959). Analysis of fecal vitamin B-6 indicated no differences between total vitamin B-6 in fecal samples of low-and high-protein basal diets (1.95 ± 0.12 and 1.71 ± 0.24 nmol of vitamin B-6/g of sample, respectively), regardless of dietary vitamin B-6 concentration.…”
Section: Discussionmentioning
confidence: 99%
“…When the level of protein in the diets was increased to either 20% or as high as 50% of the total diet, growth-related parameters indicated higher responses to PN in the diet relative to PL and PM (Table V). It has been suggested in earlier work that intestinal microorganisms may preferentially utilize PL and PM in the diet, leading to decreased availability of and therefore decreased rat responses to dietary PL and PM (Waibel et al, 1952;Davies et al, 1959). Analysis of fecal vitamin B-6 indicated no differences between total vitamin B-6 in fecal samples of low-and high-protein basal diets (1.95 ± 0.12 and 1.71 ± 0.24 nmol of vitamin B-6/g of sample, respectively), regardless of dietary vitamin B-6 concentration.…”
Section: Discussionmentioning
confidence: 99%
“…I t has been shown in several foods that pyridoxine is not stable to heat (Woodring & Storvick, 1960) and that, for example, 45-70% can be lost during the evaporation of milk, with further losses on storage (Davies, Gregory & Henry, 1959).…”
Section: Folic Acid and Pyridoxinementioning
confidence: 99%
“…The three natural forms of vitamin B6 (pyridoxine, pyridoxamine, and pyridoxal) show varying activity for poultry. Thus, pyridoxine is usually more active than pyridoxal and pyridoxamine in promoting growth (Davies et al, 1959;Luckey et al, 1945;Sarma et al, 1946). Waibel et al (1952) have reported that pyridoxal and pyridoxamine are as active as pyridoxine when autoclaved starch is the dietary carbohydrate, but less active than pyridoxine when sucrose or glucose was the carbohydrate.…”
Section: Discussionmentioning
confidence: 99%